MORPHOLOGICALLY BIVALENT AND TRIVALENT WORDS IN OLD ARMENIAN (SYNCHRONIC AND DIACHRONIC CONCEPT) - KHACHATRYAN, LALIK (Main Issues Of Pedagogy And Psychology, 2015)
Morphologically bivalent and trivalent words in Old Armenian are studied in two aspects: synchronic and diachronic. Synchronic concept distinguishes the layers of morphologically polyvalent words formed in the period of preliterary language development and as a legacy passed to Old Armenian. These words express polyvalence of parts of speech in primary form, without formative morphemes and statically exist in the word-stock of Old Armenian. Taking as a basis the Bible word-stock, the written manuscripts of classical Armenian and following their further semantic changes in the case of diachronic approach we distinguish another layer of polyvalent words that chronologically developed in Old Armenian (V-XII centuries).